2022
DOI: 10.1088/1741-4326/ac3f4d
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid simulations of beta-induced Alfvén eigenmode with reversed safety factor profile

Abstract: Based on the experimental parameters in HL-2A tokamak, hybrid simulations have been carried out to investigate the linear stability and nonlinear dynamics of BAE. It is found that the (m/n=3/2) beta-incuced Alfvén eigenmode (BAE) is excited by co-passing energetic ions with qmin=1.5 in linear simulation, and the mode frequency is consistent with experimental meuasurement. The simulation results show that the energetic ions βh, the injection velocity v0 and orbit width parameter ρh of energetic ions are importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…In the present case, for the basic-frequency case, Ω * pi = 0.6051 and f ti = 9.7674 kHz; then, the theoretically predicted frequency is about f = 0.7441 f ti = 7.2680 kHz, which is consistent with the frequency ( f LFM1 ∼ 8.0 kHz) in the plasma frame in the experiment. Similarly, for the higher-frequency branch (12,6), Ω * pi = 1.2102 and f ti = 9.7674 kHz; then, the theoretically predicted frequency is about f = 1.1387 f ti = 11.1220 kHz, which is consistent with the frequency ( f LFM2 ≈ 12.5 kHz) in the plasma frame in the experiment. It is also clearly shown that the mode frequency jumps from 7.3 kHz to 11.1 kHz, which is of the same order as the experimental observations.…”
Section: Factor: Q-profilesupporting
confidence: 78%
See 2 more Smart Citations
“…In the present case, for the basic-frequency case, Ω * pi = 0.6051 and f ti = 9.7674 kHz; then, the theoretically predicted frequency is about f = 0.7441 f ti = 7.2680 kHz, which is consistent with the frequency ( f LFM1 ∼ 8.0 kHz) in the plasma frame in the experiment. Similarly, for the higher-frequency branch (12,6), Ω * pi = 1.2102 and f ti = 9.7674 kHz; then, the theoretically predicted frequency is about f = 1.1387 f ti = 11.1220 kHz, which is consistent with the frequency ( f LFM2 ≈ 12.5 kHz) in the plasma frame in the experiment. It is also clearly shown that the mode frequency jumps from 7.3 kHz to 11.1 kHz, which is of the same order as the experimental observations.…”
Section: Factor: Q-profilesupporting
confidence: 78%
“…We now investigate the LFMs' instabilities by adopting the local equilibrium parameters of the EAST discharge #60223 evaluated at R = 2.018 m, and are B 0 = 2.0612 T, τ = 3.2204, β i = 0.0014, η i = 1.1455, r = 0.0635, δW f = −0.0056 and ni ≡ L ni /R = 0.4138. Figure 11(b) shows the dependence of mode frequencies and growth rates on Ω * pi = ω * pi /ω ti for the basic-frequency branch (6, 3) with k θ ρ Li = 0.1171 and k θ ρ Le = 0.0035, and the higher-frequency branch (12,6) with k θ ρ Li = 0.2341 and k θ ρ Le = 0.0069. The other equilibrium parameters are fixed.…”
Section: Factor: Q-profilementioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that strictly speaking the SF-magnetic configuration we used should be identified as XD according to reference [48] due to the secondary X-point being located outside the plasma domain. However, a similar configuration has been named SF in HL-2M [46,49], NSTX [50,51] as well as DIII-D [17], therefore, we still keep naming it as 'SFD', which is consistent with previous works. Nevertheless, the naming of the configuration does not influence the conclusions.…”
Section: Introductionsupporting
confidence: 77%
“…In M3D-K, the bulk plasma is described by the resistive MHD equations and the energetic ions (EPs hereafter) are described by the drift-kinetic equations, and the kinetic effects of EPs are coupled into the momentum equation through the EPs pressure tensor P h [36,37]. This hybrid model is widely applied to study the problems of the interaction between EP and MHD instabilities [3][4][5][38][39][40][41][42][43][44][45]. The main parameters are as follows.…”
Section: Experimental Phenomena and Simulation Setupmentioning
confidence: 99%